Evaluating the effect of a need-based program for caregivers on the stress, anxiety, depression, and the burden of care in families of children with attention deficit-hyperactive disorder - Sharifeh Mousavi; Saeid Pahlavanzadeh; Jahangir Maghsoudi (Wolters Kluwer Medknow Publications, 2019)
Background: Attention-deficit hyperactive disorder (ADHD) is the most common behavioral disorder of childhood, and due to its chronic nature, it would affect all the aspects of life of the child and the caregiver. Therefore, this study was conducted to determine the effect of a program based on the needs of caregivers on stress, anxiety, depression, and burden of care in families of children with ADHD. Materials and Methods: This randomized clinical trial was conducted on 70 family caregivers of children with ADHD from June to September of 2016. After convenience sampling, eligible samples were randomly allocated into two groups of control and intervention. The intervention group received the need-based educational program in eight sessions and the participants of the control group participated in two group sessions where they expressed their problems and experiences. Data were gathered through Zarit Burden Interview and Depression Anxiety and Stress Scale (DASS)-42 and then were analyzed using descriptive and inferential statistics. Results: The mean scores of stress, anxiety, depression, and burden of care had a significant difference between both groups right after and 1 month after the intervention (p < 0.001), whereas in the control group, there was no gradual decrease in the mean scores of the dependent variables. Conclusions: The need-based educational program might reduce the level of stress, anxiety, depression, and burden of care in families of children with ADHD. It is recommended to develop similar programs and evaluate them through various studies. The use of nonpharmacological treatment of these children is evident in the results.